Pulling the Trigger: On Writing the Novella Ivy - Eyrún Elíasdóttir 1994- (2017)
My creative writing final thesis, for a bachelor degree in English from the University of Iceland, is split into two halves. The first is the novella, Ivy (about 10.500 words), and the second is an exposition about the writing process (about 3.000 words). Ivy is a post-apocalyptic story about Ivy, a girl who has been kept inside all her life with her brother, aunt, and uncle because of the global war raging outside. But one day the bombs reach their home and she is forced outside and into the unforgiving world. Separated from her brother and uncle, she joins the army and learns first hand that life isn’t easy. Holding onto her hopes and dreams of finding her brother Zeke, she struggles to cope in this world of brutality. The theme of the story is the loss of innocence and war is the core of the problem. The inciting incident, and the start of the story, is war seeping into Ivy’s life. It takes her away from her home and her brother. The conflict in the story is rooted in Ivy’s own psychological problems and how she deals with her experiences. She is influenced by the people around her, and the troubling events in the rising action which lead her down a dark path. In the climax, after undergoing great changes, Ivy is forced to make a decision and she loses her innocence. The exposition details the writing and editing process, its obstacles and the decisions made that shaped the plot and characters of the novella. It goes through the transformative process of starting the thesis a year ago and what influenced me to write about this. The exposition consists of six chapters, each one detailing a specific aspect of the writing process. Firstly, decisions and plot, then looking on the editing process, characterisation, descriptions and setting, and finally tweaking and inspirations.